2020
DOI: 10.1111/dth.13722
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy, speed of improvement and safety of apremilast for the treatment of adult Psoriasis during COVID‐19 pandemic

Abstract: Time to improvement is a crucial characteristic for effective treatments of chronic inflammatory conditions, such as psoriasis. Apremilast is a recently approved drug, belonging to the small molecule phosphodiesterase 4 inhibitors, whose optimal safety and efficacy profile is somewhat affected by slow activity rate in clinical trials. Real world case series are suggesting a more consistent improvement, and with this additional personal investigation on 48 patients, we signal that 58% of patients achieved Psori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…7 Results in realworld settings have further reinforced the safety and efficacy of apremilast on psoriasis patients during the COVID-19 pandemic. 13 In conclusion, apremilast does not seem to particularly increase susceptibility to infection and can be considered a safe alternative for both infected and uninfected COVID-19 patients. IL-17 inhibitors seem to have also a relatively safe profile, while with systemic agents and TNFα inhibitors cautions are advised.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…7 Results in realworld settings have further reinforced the safety and efficacy of apremilast on psoriasis patients during the COVID-19 pandemic. 13 In conclusion, apremilast does not seem to particularly increase susceptibility to infection and can be considered a safe alternative for both infected and uninfected COVID-19 patients. IL-17 inhibitors seem to have also a relatively safe profile, while with systemic agents and TNFα inhibitors cautions are advised.…”
Section: Discussionmentioning
confidence: 87%
“…12 Several studies have reported a good efficacy and an excellent safety profile for apremilast in the treatment of psoriasis and psoriatic arthritis. 12,13 Regarding virus infections, large studies have shown a significant decrease of serious infection rate in apremilast-treated patients. 14 In a prospective safety study on the long-term safety of different medications for psoriasis, authors reported that apremilast patients had a lower risk of infections and infestations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed many authors reported that none of the patients treated with Apremilast developed COVID-19 related symptoms. 40 We combined the present evidences from this paper with the management suggestion already in place, 41,42 and developed an algorithm for the management of patients treated with DMARDs during this pandemic ( Figure 2). The main limitation of our pooled analysis is the small sample size, possibly not allowing adequate statistical power, even if representing an insightful description of the now available best knowledge about the topic.…”
Section: Discussionmentioning
confidence: 99%
“…В настоящее время мнение экспертов заключается в том, что апремиласт является одним из более безопасных вариантов лечения псориаза средней и тяжелой степени тяжести с учетом его специфического неиммуносупрессивного механизма действия. Недавний опыт лечения больного с COVID-19, который продолжал лечение апремиластом во время двусторонней пневмонии и полностью выздоровел, подтверждает безопасность и совместимость с лечением критически больных пациентов [11][12][13].…”
Section: риски возникновения инфекций у пациентов с псориазом получаunclassified